2014
DOI: 10.1124/dmd.113.055475
|View full text |Cite
|
Sign up to set email alerts
|

6β-Hydroxycortisol Is an Endogenous Probe for Evaluation of Drug–Drug Interactions Involving a Multispecific Renal Organic Anion Transporter, OAT3/SLC22A8, in Healthy Subjects

Abstract: 6b-Hydroxycortisol (6b-OHF) is a substrate of the organic anion transporter 3 (OAT3) and the multidrug and toxin extrusion proteins MATE1 and MATE-2K in the corresponding cDNA-transfected cells. This study aimed to examine the contribution of OAT3 and MATEs to the urinary excretion of 6b-OHF in humans using the appropriate in vivo inhibitors, probenecid and pyrimethamine, for OAT3 and MATEs, respectively. Oat3(-/-) mice showed significantly reduced renal clearance of 6b-OHF (CL renal, 6b-OHF ) compared with wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…Recently, many researchers have focused on the mechanism of drug-induced hyperbilirubinemia (Zucker et al, 2001;Campbell et al, 2004;Chang et al, 2013;Wlcek et al, 2013;Chiou et al, 2014); however, the exact mechanism of drug-induced hyperbilirubinemia in humans and the relationship between the biomarkers and DDI from a quantitative perspective have not been elucidated. In other cases, previous studies have shown that when the renal transporters were inhibited by drugs, the plasma concentrations of creatinine, N-methylnicotinamide, and 6b-hydroxycortisol increased with the inhibition of OCT2 and/or MATEs, MATEs, and OAT3 by drugs, respectively (Imamura et al, 2011(Imamura et al, , 2014Ito et al, 2012). The utility of an endogenous substrate as a biomarker for transporter inhibition has been a topic of great interest.…”
Section: Biomarkers For Inhibition Of Transportersmentioning
confidence: 99%
“…Recently, many researchers have focused on the mechanism of drug-induced hyperbilirubinemia (Zucker et al, 2001;Campbell et al, 2004;Chang et al, 2013;Wlcek et al, 2013;Chiou et al, 2014); however, the exact mechanism of drug-induced hyperbilirubinemia in humans and the relationship between the biomarkers and DDI from a quantitative perspective have not been elucidated. In other cases, previous studies have shown that when the renal transporters were inhibited by drugs, the plasma concentrations of creatinine, N-methylnicotinamide, and 6b-hydroxycortisol increased with the inhibition of OCT2 and/or MATEs, MATEs, and OAT3 by drugs, respectively (Imamura et al, 2011(Imamura et al, , 2014Ito et al, 2012). The utility of an endogenous substrate as a biomarker for transporter inhibition has been a topic of great interest.…”
Section: Biomarkers For Inhibition Of Transportersmentioning
confidence: 99%
“…Other metrics of cortisol and its metabolites have been explored, such as the formation clearance of 6b-hydroxycortisol and a summed formation clearance of 6b-hydroxycortisol and 6b-hydroxycortisone (Luo et al, 2009;Peng et al, 2011). Because 6b-hydroxycortisol was found to be a substrate of the renal organic anion transporter 3, urinary 6b-hydroxycortisol/cortisol metabolic ratios may be affected if organic anion transporter 3 function is altered (Imamura et al, 2014).…”
Section: Interindividual Variability In Cyp2d6-mediated Drugmentioning
confidence: 99%
“…Therefore, the availability of endogenous biomarkers to assess transporter activities during early drug development would have substantial benefits for the pharmaceutical industry in order to avoid expensive clinical trials and also minimize the risk of late-stage failures and even drug withdrawal. In this regard, many attempts have been made to identify endogenous compounds that could reflect the activities of enzymes and transporters, such as CYP3A4 (Kanebratt et al, 2008;Diczfalusy et al, 2011;Shin et al, 2013;Kasichayanula et al, 2014), CYP2D6 (Tay-Sontheimer et al, 2014), MATEs (Ito et al, 2012;Kato et al, 2014;Müller et al, 2015), and OAT3 (Imamura et al, 2014) to improve prediction of DDI. However, as far as we know, no validated in vivo clinical endogenous probe of OATP1B has been identified.…”
Section: Introductionmentioning
confidence: 99%